Stem Cell Treatment For Diabetes - SAKTHIVEL .K; RAJESH .C; SENTHAMARAI .R (International Journal of Pharma and Bio Sciences, 2010)
Diabetes is often called the "silent killer" because it attacks the body slowly and stealthily. Newly diagnosed adult diabetes patients are usually not overly concerned about it since their symptoms are often no more serious than frequent urination and increased thirst. Many other patients have no symptoms at all. It’s actually a group of diseases characterized by abnormally high levels of the sugar glucose in the bloodstream. This excess glucose is responsible for most of the complications of diabetes, which include blindness, kidney failure, heart disease, stroke, neuropathy, and amputations. Diabetics using stem-cell therapy have been able to stop taking insulin injections for the first time, after their bodies started to produce the hormone naturally again. Diabetes patients are usually treated by injecting the stem cells into the pancreatic artery via catheter. Patients who cannot safely undergo the catheterization procedure may elect to receive the stem cells intravenously. Both methods are outpatient procedures that require patients to stay in hospital for 4 or 5 nights.